DETERMINAN KEPUTUSAN PEMBELIAN PADA PRODUK SKINCARE WHITELAB DI CILACAP - Intania, Nesi Agesti; Jayanti, Esih; Werdiasih, Rustina Dewi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This research seeks to examine the influencecelebrity endorsement (X1), e-WOM (X2), and brand equity (X3) on consumer behavior in purchasing Whitelab skin care products in Cilacap (Y). Data were collected through distributing questionnaires to consumers of Whitelab skin care products in the Cilacap area. The sampling method applied was purposive sampling, so that 100 respondents were successfully obtained. The analysis methods applied include validity and reliability tests, the method of consecutive intervals (MSI), and the regression model's validity and reliability were checked using traditional assumption tests, such as tests for heteroscedasticity, multicollinearity, normalcy, and linearity. In addition, multiple linear regression analysis was conducted as well as hypothesis testing utilizing the t-test, F-test, and coefficient of determination (R²). The study comes to the conclusion that celebrity endorsement has a significant impact on consumers' purchasing choices regarding Whitelab skincare products. E-WOM has a huge impact on consumers' decsions to purchase Whitelab skincare products. Brand equity has a major influence on consumer choice in purchasing Whitelab skin care products. At the same time, celebrity endorsement, e-WOM, and brand equity serve as important factors in consumers' choice to purchase Whitelab skin care products.